Alternatives in polymerization contraction stress management - Roberto R. Braga; Jack L. Ferracane (University of São Paulo, 2004)
Polymerization contraction stress of dental composites is often associated with marginal and interfacial failure of bonded restorations. The magnitude of the stress depends on the composite's composition (filler content and matrix composition) and its ability to flow before gelation, which is related to the cavity configuration and curing characteristics of the composite. This article reviews the variations found among studies regarding the contraction stress testing method, contraction stress values of current composites, and discusses the validity of contraction stress studies in relation to results from microleakage tests. The effect of lower curing rates and alternative curing routines on contraction stress values is also discussed, as well as the use of low elastic modulus liners. Moreover, studies with experimental Bis-GMA-based composites and recent developments in low-shrinkage monomers are described.